Change in gastric-lipase adsorption on lipid layer by stigmasterols - Shin, Gounhanul (2024)
Gastric-lipase (GL) binding to a lipid layer was investigated for the phase of the layer adjusted with the ratio of stigmasterol to the lipid using surface plasmon resonance. While the layer was formed on the hydrophobic surface, more stigmasterol led to lower surface density only in the dipalmitoylphosphatidylcholine (DPPC) layer. The addition of stigmasterol was believed to transform the phase (condensed liquid-phase) of DPPC layer closer to the phase (expanded liquid-phase) of dioleoylphosphatidylcholine (DOPC) layer. At a ratio greater than 15:85, the effect of the stigmasterol on the DPPC was saturated. The adsorption behavior of GL showed the similar trend with the lipid formation. The adsorption increased with the increase in the ratio of stigmasterol to lipid up to 15:85. On the DOPC layer of the expanded liquid-phase, the most adsorption seemed to occur and was indistinguishable from that in the DPPC layer of 15:85. The surface density of the adsorbed GL was interpreted into the fraction of the stigmasterol-dependent DPPC, 0.33, 0.67, and 1.00 for 10:90, 5:95, and 0:100 of DPPC. Furthermore, the equilibrium constant was between 1 × 1013»M-1 and 2 × 1013»M-1 and the kinetics of the adsorption showed an increase in the adsorption rate constant with the increase of the ratio up to 15:85.